Who studies religion at Advanced level: Why and to what effect?*. Issue 3 (1st September 2016) - Francis, Leslie J.; Astley, Jeff; Parker, Stephen G.
Abstract: This study was established to profile students currently studying religion at Advanced level (A level) in terms of their demography, motivation, experience and attitudes. Eight specific areas were identified for examination: their personal motivation to study religion at A level, the personal challenges posed by the subject, their personal experience of studying the subject, their growth in understanding stimulated by the subject, the impact of their study on respecting religious diversity, the impact on their personal development, the impact on spiritual and religious development, and the connection between studying religion at A level and their personal faith. Data were provided by 462 students at the end of the first year of A level study. Key findings demonstrated that 78% of students opted for the subject because they enjoyed their earlier experiences of religious studies in school, that 80% of students have become more tolerant of religious diversity, and that only 7% of students feel that studying religion at A level has undermined their personal religious faith while three times that number feel that it has affirmed their religious faith.